The Relationship Between the State, the Market and Society in Vietnam: An Analysis from the Constitutional Law Perspective - Giao, Vu Cong (VNU Journal of Science: Legal Studies, 2025)
The article delves into the relationship between the state, the market and society, primarily from the perspectives of neo-liberalism and state interventionism and highlights the difference between these approaches. On this basis, the author analyzes the state-market-society relationship in Vietnam in the contemporary era, as evidenced in the Constitutions from 1946 to 2013. The author asserts that this relationship has continually adapted to the country's historical context since independence, aligning with the global trend. However, there are still some areas that require attention, particularly in economic policy and ensuring substantive public participation in social governance.